Analisis Putusan Perceraian terhadap Nafkah Anak dalam Praktik di Pengadilan Agama - Tri Alviani; Muhammad Fathinnuddin (HUMANIORUM, 2026)
Child support usually occurs after a divorce is finalized by the Religious Court. According to Indonesian law, after a panel of judges has decided to dissolve a marriage between a husband and wife, the husband is obligated to provide child support. However, in practice, husbands sometimes fail to comply with this decision, particularly when it comes to providing child support until the child reaches adulthood. The responsibility to provide child support remains the husband's, as stipulated in the decision of the Panel of Judges at the Tangerang City Religious Court. If a husband fails to provide child support, the wife and children may be neglected or neglected, a common problem after divorce. As a result, the wife is forced to support herself and her children's needs. Generally, the husband voluntarily provides child support. The court cannot immediately execute the decision without a request from the injured party. However, wives often face obstacles, both due to a lack of understanding of the legal process and the relatively high cost of enforcement.